(3ahGFO QLGdjIs - (3GdnqWnHGnWnHGFj GdHQhLQOj, GHf GdeQJVi, HMQ GdYdhe, eMeO egOj Hf eQJVi Hf eMeO, J (B1212 (3g`s ((3eMeO Hf EHQGgje GdMSjfjs)
(3ChdgG (B:s
(3Bd CHj QGaY, ef CQaY HjhJ GdTjYI hCYdGgG TCfG(B...s
(3BNQgG (B:s
(3Yf eTGjN GdMOjK hGdKdGKI QVhGf Gddg Ydjge(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B113s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdMOjK hGdeUWdMs